Teachers' Concerns with the Implementation of Practical Work in the Physical Sciences Curriculum and Assessment Policy Statement in South Africa. Issue 1 (2nd January 2019) - Oguoma, Enid; Jita, Loyiso; Jita, Thuthukile
Abstract : A new Curriculum and Assessment Policy Statement (CAPS) was introduced in South Africa in 2012 to, among others, drive a learner-centred and constructivist approach to practical work in the high school subject Physical Sciences. This study investigates teachers' concerns with the implementation of practical work in Physical Sciences. A survey of 81 high school physical science teachers' concerns was conducted in a school district in South Africa. Participants were selected from 52 schools by means of convenience sampling. The seven stage concerns-based adoption model was used to identify teachers' stages of concern on the practical component of CAPS. The findings indicate that 69% of the participants ( n = 47) had management concerns of high significance ( p = 0.51), while the collaboration and consequence concerns were only slightly significant ( p = 0.96). With regards to CAPS experience, respondents who had been implementing CAPS for less than three years had more personal concerns compared with those who had been executing it for three to four years. Equally, respondents with less experience with CAPS had marginally more management concerns compared with respondents with more experience. These trends were also observed with the collaboration and refocusing concerns suggesting that teachers with less CAPS experience worry more about their ability to manage practical work and to make laboratory activities workable in their contexts. The paper concludes with a discussion on the variety of concerns and how these might be addressed through targeted teacher professional development support.